Congenital Heart Diseases Impair Female Fertility - Chien, Shao-Ju; Lin, Ying-Jui; Lo, Mao-Hung; Huang, Chien-Fu; Yang, Yao-Hsu (Frontiers in Pediatrics, 2021)
Background: The objective of this research was to evaluate the fertility of Taiwanese women with diagnoses of congenital heart diseases (CHDs). The study also investigated how different forms of CHDs may have variously influenced fertility. Methods: We directed this nationwide, population-based and retrospective matched-cohort research by using data from the Taiwan National Health Insurance Research Database. The CHD group (n = 6602) included women with congenital structural heart diseases, aged 16–45 years in 2000. The non-CHD group (n = 6602) was matched according to sex, gender, urbanization and income, and. The outcomes, involving live birth, abortion, and fertility rates, were followed until the end of 2013. Poisson regression was used to evaluate the incidence rate ratios (IRRs). Results: The CHDs had an inferior rate of live births (IRR 0.74 [95% CI 0.71–0.78]) than the non-CHD group. There was also a lower fertility rate in the CHD group (IRR 0.81 [95% CI 0.78–0.84]) than the non-CHD group. Abortion rates between the two groups were similar. Conclusion: Congenital structural heart disease compromises female fertility, even among patients with simple forms of CHDs. It is suggested that pregnant patients with CHDs are early appeared to and advised personally with multidisciplinary care to improve their outcomes.